Cost Compliance Analysis of Real Therapy and INA-CBG’s of Chemotherapy Breast Cancer Inpatien At 2017 Dr. Moewardi Surakarta Hospital - Dewi, Belinda Arbitya; Oetari, Oetari; Andayani, Tri Murti (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Observational research using a restrospective design from a hospital perspective. Samples of all claim files and medical records of breast cancer chemotherapy patients with codes C-4-13-I, C-4-13-II, and C-4-13-III in 2017. Analysis of the suitability of the cost of therapy with INA-CBG's rates with one sample t-test and factors that influence the cost of therapy with multivariate analysis. The results showed there were 113 treatment episodes of 72 patients, of which women aged <45 years were most affected. Difference between the real cost of hospitalized breast cancer and INA-CBG's rates in class 3 treatment C-4-13-I severity level Rp. -62,187,362, C-4-13-II of Rp. 6,159,896, C-4-13-III Rp. 64,042,570. Based on all severity values P <0.05, means the average cost of treating breast cancer with all different severity levels based on INA-CBG’s 2016 rates.